2018
DOI: 10.1016/j.rbmo.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the clinical efficacy of vaginal progesterone for luteal phase support in assisted reproductive technology cycles

Abstract: Vaginal progesterone via capsule, gel or tablet is the most common route for luteal phase support (LPS) in Europe. Although there is a wealth of data comparing products used at other stages of assisted reproductive technology cycles, there is a lack of systematically identified evidence comparing the wide range of vaginal progesterone products. This systematic review queried the MEDLINE, Embase and Cochrane Library databases on 30 June 2016 to identify head-to-head randomized controlled trials (RCTs) comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Studies have claimed that due to the first-pass effect through the liver, oral progesterone was the least effective form, contrary to intramuscular, which was reported to be the most efficient 11. Many studies have confirmed that vaginal administration of micronized progesterone tablets and progesterone vaginal gel have similar effects on persistent pregnancy rate, but progesterone gel is more convenient to use 1216. There have not been any studies undertaking comparative study of the PK parameters of Yimaxin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have claimed that due to the first-pass effect through the liver, oral progesterone was the least effective form, contrary to intramuscular, which was reported to be the most efficient 11. Many studies have confirmed that vaginal administration of micronized progesterone tablets and progesterone vaginal gel have similar effects on persistent pregnancy rate, but progesterone gel is more convenient to use 1216. There have not been any studies undertaking comparative study of the PK parameters of Yimaxin.…”
Section: Discussionmentioning
confidence: 99%
“…The present study established a positive association between first trimester NT and birthweight, although our study includes non-IVF patients. Some studies in literature demonstrated increased NT with the use of exogenous progesterone in the first trimester (21,22) , and it is widely known that progesterone is used in the luteal phase and the first trimester as a worldwide standard procedure in IVF patients (23,24) . Accordingly, the current study population was selected from non-IVF patients and those who did not use progesterone in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…A second follicular wave is indicated considering the high E2 levels recorded and evident through ultrasound evaluation [3]. However, due to high levels of progesterone—following the original ovulation and entering the luteal phase [58]—the SFW fails to lead to ovulation of the luteal phase Graafian follicle. It is evident that progesterone produced by the corpus luteum in luteal phase may contribute to the pituitary suppression through negative feedback, with the consequence of an anovulatory follicular wave [45].…”
Section: Discussionmentioning
confidence: 99%